HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PASIEN YANG MENJALANI KEMOTERAPI DI RUANG ANYELIR RSUD ARIFIN ACHMADPROVINSI RIAU - Satria ' Adipo; Jumaini ' '; Siti Rahmalia Hairani Damanik (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research to identify the relationship of family support with anxiety level of chemotherapy patients in Anyelir Ward General Hospital Arifin Achmad Riau Province. This research is descriptive study with cross sectional approach. The samples taken from patients with cancer who followed chemotherapy in Anyelir Ward GeneralHospitalArifin Achmad Riau Province with 39 respondents through purposive sampling technique. The data taken by questionnaire that already tested for validity and reliability. The analysis used univariate and bivariate with chi-square test. The results showed p value was 0,022 (p value < 0,05), which means there is a relationship between family support with the anxiety level of chemotherapy patients. The results recommend to health workers to improve the psychosocial nursing care and remind family the importance of family support to minimize the anxiety on chemotherapy patients. Keywords: Family support, the anxiety, chemotherapy